AÇÃO PROFILÁTICA DO RANELATO DE ESTRÔNCIO NAS ALTERAÇÕES MORFOLÓGICAS DE OSTEOARTRITE EXPERIMENTAL. - CARVALHO, Heetor Campora Oliveira (2018)
Introduction: Osteoarthritis (OA) is a multifactorial disease as a result of several and complex mechanisms interacting to cause joint damage. There is no cure for OA, but progression can be controlled. Many drugs can act to decrease manifestations of OA, such as strontium ranelate (RnSr), but its preventive effect on joint injuries has not yet been demonstrated. Aim: To evaluate the prophylactic effect of RnSr in an experimental model of osteoarthritis in rats' knees. Methods: The animals were divided into 3 groups, called Prophylactic, Control and Naïve, with 6 mice each. Prophylactic group received RnSr at the dose of 250 mg/kg orally for 07 days until OA induction; Control group received 0.9% saline solution also orally and for the same period, being submitted to OA induction; and Naïve group had only standard feeding, not submitted to OA induction. Twenty-nine days after OA induction animals were euthanized, knee Xray was performed, knee joint cartilage and synovial membrane were collected. Results: Radiographic images showed the greatest changes in Control group, with statistical significance (p<0.05). Regarding to articular cartilage changes no alteration were found in Naïve group, however, there was a significant change in Control group comparing to Prophylactic group (p<0.05). Synovial membrane was not affected by the treatment, since the results were similar in all groups (p>0.005) In the evaluation of the synovial membrane, no statistical difference was observed between the study groups (p>0.05). Conclusion: Results indicate that RnSr is a drug with potential prophylactic effect on OA, decreases changes in the articular cartilage and the degenerative pattern of knee joints.